2017
DOI: 10.1111/efp.12344
|View full text |Cite
|
Sign up to set email alerts
|

Widespread latent infection of Cryptostroma corticale in asymptomatic Acer pseudoplatanus as a risk for urban plantations

Abstract: Summary Sooty bark disease (SBD) caused by the pathogen Cryptostroma corticale is currently one of the risks to the population of Acer pseudoplatanus in Europe. After a number of records of symptomatic and dead trees in Prague, assessment of the latent non‐symptomatic stage of SBD was questioned as a means to forecast the health risk of the A. pseudoplatanus population. We used two methods of early detection of C. corticale in non‐symptomatic trees: cultivation from wood tissue on agar plates and a culture‐fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 14 publications
7
36
1
Order By: Relevance
“…Tree mortality can be affected by other factors, such as wind disturbance, snow damage, pest emergence, fires or pathogens, which we did not include in our study. For instance, Fraxinus excelsior mortality has been related directly to the pathogen Chalara fraxinea (Kowalski, 2006), and Acer pseudoplatanus is threatened by several pathogens spreading rapidly in Europe [e.g., Eutypella parasitica and Cryptostroma corticale (Kelnarová et al., 2017; Ogris et al, 2006)]. The relatively low variance explained by our models for some species ( Acer pseudoplatanus , Fraxinus excelsior , B. pendula , Castanea sativa and Pinus nigra ) could be related directly to these missing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Tree mortality can be affected by other factors, such as wind disturbance, snow damage, pest emergence, fires or pathogens, which we did not include in our study. For instance, Fraxinus excelsior mortality has been related directly to the pathogen Chalara fraxinea (Kowalski, 2006), and Acer pseudoplatanus is threatened by several pathogens spreading rapidly in Europe [e.g., Eutypella parasitica and Cryptostroma corticale (Kelnarová et al., 2017; Ogris et al, 2006)]. The relatively low variance explained by our models for some species ( Acer pseudoplatanus , Fraxinus excelsior , B. pendula , Castanea sativa and Pinus nigra ) could be related directly to these missing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy trees can be asymptomatically affected by C. corticale as an endophyte while impairment of the tree, e.g., by drought may lead to a higher risk to contract on SBD [4,26]. It is to assume that latent infections by C. corticale are widespread, also in urban plantations of maples [14].…”
Section: Sooty Bark Disease Of Maples Caused By Cryptostroma Corticalementioning
confidence: 99%
“…The thermophilic C. corticale profits of lack of water and heat stress in long-lasting summers [25]. Further stressors for the maples such as flooding, high nitrogen oxide concentrations and unfavourable on-site conditions also favour the spread of SBD [12][13][14]. It was found that urban conditions with climate extremes, higher temperatures and air pollution at traffic roads or paths lead to more SBD infection of sycamores [14].…”
Section: Sooty Bark Disease Of Maples Caused By Cryptostroma Corticalementioning
confidence: 99%
See 2 more Smart Citations